Novel environment-friendly colored permeable asphalt concrete and preparation method thereof
By using environmentally friendly materials such as polymer modified asphalt and reinforced fibers in permeable asphalt concrete, the durability problem of traditional permeable asphalt concrete under high temperature conditions is solved, which significantly improves the stability and crack resistance of the road surface and extends the service life And reduce the release of harmful substances.
Patent Information
- Application Number
- CN202411211889.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-13
AI Technical Summary
Traditional permeable asphalt concrete has poor durability under high temperature conditions, is prone to softening, blocked pores, aging and cracking, and is not durable to vehicle loads and environmental factors.
Modify the asphalt with polymer modified asphalt, especially styrene-butadiene-styrene (SBS) block copolymer, enhance its elasticity and crack resistance, and add silane modified polymer and EVA plasticizer , combines reinforced fibers and mineral powder to improve bonding and fatigue resistance.
It significantly improves the stability and durability of asphalt concrete, extends the service life of the road surface, reduces the release of harmful substances, and complies with environmentally friendly building materials standards.
Abstract
Description
Technical Field
[0001] The present application relates to the field of concrete, and more specifically, to a novel environmentally friendly colored permeable asphalt concrete and a preparation method thereof. Background Art
[0002] As urban areas continue to expand, the proportion of hard roads increases year by year, resulting in the inability of rainwater to effectively infiltrate, and the problem of waterlogging is becoming increasingly serious. Traditional asphalt pavements are not permeable, and rainwater accumulates on the road surface, which not only affects traffic but may also damage the roadbed. Permeable asphalt concrete can effectively solve the problem of rainwater accumulation and improve the city's rainwater management capabilities through its special structural design.
[0003] Permeable asphalt concrete has many significant technical features. First, it is highly permeable, with a porosity usually between 15% and 25%, which can quickly penetrate rainwater, reduce surface runoff, and replenish groundwater resources. Secondly, by adding different pigments, it can present a variety of colors to meet different design requirements and enhance the aesthetics of urban landscapes. Environmentally friendly colored permeable asphalt concrete is widely used in urban construction. By using this material, urban roads and sidewalks can effectively reduce water accumulation and improve the safety and comfort of driving and pedestrians. In parks and scenic spots, permeable asphalt concrete can be integrated with the surrounding natural environment, enhance the landscape effect, and improve the growth environment of soil and plants. The use of this material in parking lots can reduce water accumulation, enhance the experience of vehicles and pedestrians, and reduce environmental impact.
[0004] However, permeable asphalt concrete still has the problem of poor durability. Under long-term high temperature conditions in summer, permeable asphalt concrete pavement will become soft. If the softened pavement is subjected to heavy pressure, the surface material will be squeezed and the pores will be blocked, thus losing its original permeability. In addition, the pavement surface is prone to aging and cracking due to long-term exposure to sunlight. Coupled with the frequent rolling of vehicle tires, the pavement is prone to friction and shedding. Summary of the invention
[0005] In order to improve the durability of permeable asphalt concrete, the present application provides a new type of environmentally friendly colored permeable asphalt concrete and a preparation method thereof.
[0006] The new environmentally friendly colored permeable asphalt concrete provided in this application adopts the following technical solution: A novel environmentally friendly colored permeable asphalt concrete and a preparation method thereof, comprising the following components in parts by weight: 10-20 parts of polymer modified asphalt, 2-3 parts of color pigment, 1-5 parts of additive, 40-50 parts of fine aggregate, 20-30 parts of coarse aggregate, 10-15 parts of reinforcing fiber and 5-10 parts of mineral powder. The polymer modified asphalt is asphalt modified by styrene-butadiene-styrene block copolymer.
[0007] By adopting the above technical solution, by introducing polymer modified asphalt, especially by using styrene-butadiene-styrene (SBS) block copolymer to modify asphalt, the elasticity, crack resistance and weather resistance of asphalt are significantly enhanced. This modification enables asphalt concrete to maintain better stability and durability under temperature changes, vehicle loads and environmental factors, and prolongs the service life of the road surface. The introduction of reinforcing fibers effectively improves the tensile strength and fatigue resistance of concrete, making the road surface more resistant to the formation and expansion of cracks. After the mineral powder is combined with asphalt, it can form asphalt mortar, which can enhance the bonding force between asphalt and aggregate, and improve the overall strength of the mixture. At the same time, an appropriate amount of mineral powder can also improve the physical adsorption capacity and chemical adsorption capacity of the asphalt mixture, produce more structural asphalt, reduce the generation of free asphalt, and thus improve the cohesion of the mixture.
[0008] Optionally, the preparation method of the polymer modified asphalt is: Heat the asphalt to 160-180°C and keep it warm to make it completely melted, add 5-10% of the total mass of the asphalt styrene-butadiene-styrene block copolymer to the asphalt, and keep stirring for 30-60 minutes; While maintaining the temperature of the asphalt, add 0.3-1% of the total mass of the asphalt silane-modified polymer and 0.1-0.5% of diisodecyl phosphite, and continue stirring for 10-20 minutes. Then add 1-2% of the total mass of the asphalt EVA plasticizer and continue stirring for 10-15 minutes to ensure uniform mixing to obtain polymer modified asphalt.
[0009] By adopting the above technical scheme, by adding styrene-butadiene-styrene (SBS) block copolymer and fully stirring at high temperature, SBS and asphalt form a good blending system. The addition of SBS significantly improves its high temperature stability and low temperature crack resistance, so that the modified asphalt can still maintain good flexibility and stability in an environment with large temperature changes. The addition of silane-modified polymer and diisodecyl phosphite, as effective antioxidants and stabilizers, can slow down the aging rate of asphalt under conditions such as light, oxygen and high temperature, and extend the service life of asphalt. These two additives interact with the asphalt molecular chain to form a protective layer to prevent the breakage and degradation of the asphalt molecular chain. The addition of EVA plasticizer reduces the viscosity of asphalt and improves its fluidity, making asphalt easier to mix evenly during processing and reducing processing energy consumption. The additives used in the entire modification process are all environmentally friendly materials, non-toxic and harmless, and will not cause harm to the environment and human health. At the same time, the modified asphalt can also reduce the release of harmful substances during use, which meets the environmental protection requirements of modern building materials.
[0010] Optionally, the preparation method of the silane-modified polymer is: Dissolve polyurethane in toluene to form a uniform solution, add γ-methacryloxypropyltrimethoxysilane to the polyurethane solution, the addition amount of γ-methacryloxypropyltrimethoxysilane is 4-8% of the mass of the polyurethane, stir evenly, add dicumyl peroxide to the mixed solution, the addition amount of dicumyl peroxide is 0.5-2% of the mass of the polyurethane, control the reaction temperature at 80-120°C, and the reaction time is 2-4h; After the reaction is completed, the solvent is recovered by distillation to obtain a concentrated solution of the silane-modified polymer, and the concentrated solution is dried to obtain the silane-modified polymer.
[0011] By adopting the above technical solution, the siloxane group in the silane coupling agent can form a chemical bond with the minerals in the asphalt, while the acrylate group at the other end can be compatible with organic polymer materials such as polyurethane. This "bridge" effect significantly enhances the interfacial bonding between polyurethane and inorganic materials such as asphalt, and improves the overall performance of the asphalt mixture. The siloxane segment in the silane-modified polymer has excellent water resistance and weather resistance, and can effectively resist the erosion of moisture, oxygen and ultraviolet rays. This property enables the modified asphalt to maintain good stability and durability under extreme environments. The solvents (such as toluene) used in the preparation process are recovered by distillation after the reaction is completed, reducing the emission of harmful substances. At the same time, the silane-modified polymer itself is also an environmentally friendly material that will not cause harm to the environment and human health.
[0012] Optionally, the reinforcing fiber includes one or both of basalt fiber and polyphenylene sulfide fiber.
[0013] By adopting the above technical scheme, basalt fiber has the characteristics of high strength and high modulus, which can significantly improve the tensile strength and fatigue resistance of permeable asphalt concrete. This helps to resist the stress caused by vehicle load and temperature changes, and reduce the formation and expansion of pavement cracks. The addition of basalt fiber helps to improve the thermal stability of concrete, reduce the thermal expansion and contraction effect caused by temperature changes, and maintain the flatness and stability of the pavement. Polyphenylene sulfide fiber has good heat resistance, and its products can withstand temperatures up to 190°C. The introduction of polyphenylene sulfide fiber in permeable asphalt concrete can improve the high temperature resistance of the pavement and reduce the softening and deformation of the pavement at high temperatures. Polyphenylene sulfide fiber has good resistance to chemical reagents and hydrolysis, and can resist the erosion of various chemical substances. The introduction of polyphenylene sulfide fiber in permeable asphalt concrete can improve the stability of pavement materials in harsh environments. When basalt fiber and polyphenylene sulfide fiber are added to permeable asphalt concrete as reinforcing fibers at the same time, the advantages of both can be combined to further improve the performance of concrete.
[0014] Optionally, the fine aggregate is selected from one of silica sand or quartz sand, and the coarse aggregate is selected from one of basalt or granite crushed stone.
[0015] By adopting the above technical solutions, silica sand and quartz sand have high hardness and wear resistance, which enables the road surface to maintain good flatness and durability under long-term use. Silica sand and quartz sand are chemically inert and are not easy to react with the chemical components in asphalt, thus ensuring that the long-term performance of the road surface is not affected. Basalt and granite are both hard rocks with high compressive strength and wear resistance. As coarse aggregates, they can significantly improve the bearing capacity and durability of the road surface, allowing the road surface to maintain good performance under heavy traffic.
[0016] Optionally, the additive includes 60-70% recycled wood pulp and 30-40% recycled glass powder, wherein the recycled wood pulp is a pulp obtained by removing impurities from recycled waste paper and wood and crushing them with water, and the recycled glass powder is a powder obtained by grinding recycled waste glass to 0.05-0.1 mm.
[0017] By adopting the above technical solution, recycled wood pulp is obtained by recycling waste paper and wood, removing impurities, adding water and crushing, realizing the reuse of waste resources, reducing dependence on native wood, and helping to save natural resources. The fiber structure in the recycled wood pulp helps to enhance the strength and toughness of the material, improve the bearing capacity and durability of the road surface. The main component of glass powder is silicon dioxide, which has high hardness and wear resistance, and can enhance the wear resistance and durability of the material. The recycling and reuse of waste glass reduces the exploitation of natural resources and reduces the pollution of waste glass to the environment, which is in line with the concept of environmental protection and sustainable development.
[0018] In the second aspect, the present application provides a method for preparing a novel environmentally friendly colored permeable asphalt concrete, which adopts the following technical solution: A method for preparing a new type of environmentally friendly colored permeable asphalt concrete, comprising the following steps: In the heating equipment, the polymer modified asphalt is heated to 160-170°C, and color pigments, coarse aggregates, fine aggregates, and reinforcing fibers are added and stirred evenly. During the stirring process, mineral powder and additives are added, and after stirring evenly, a new type of environmentally friendly colored permeable asphalt concrete is obtained.
[0019] In summary, this application has the following beneficial effects: 1. Since the new environmentally friendly colored permeable asphalt concrete of this application is modified by SBS block copolymer to enhance elasticity, crack resistance and weather resistance, the recycling of mineral powder reduces waste emissions, and the addition of reinforcing fibers significantly improves the tensile strength and fatigue resistance of concrete, which together ensure the stability and durability of the road surface in a changing environment and promote sustainable road construction.
[0020] 2. In the present application, preferably, styrene-butadiene-styrene (SBS) block copolymer is added under high temperature stirring, which significantly improves the high temperature stability and low temperature crack resistance of asphalt. At the same time, silane-modified polymer and diisodecyl phosphite are used as antioxidant stabilizers to effectively delay asphalt aging and extend its service life. EVA plasticizer reduces asphalt viscosity, enhances its fluidity, and optimizes processing performance. The entire modification process uses environmentally friendly materials, which are non-toxic and harmless, protecting the environment and human health. In addition, the modified asphalt can reduce the release of harmful substances during application, which fully meets the standards of modern environmentally friendly building materials.
[0021] 3. The present application preferably uses the fiber structure in the recycled wood pulp to help enhance the strength and toughness of the material, improve the bearing capacity and durability of the road surface, and realize the reuse of waste resources. Glass powder can enhance the wear resistance and durability of the material. At the same time, the recycling and reuse of waste glass is in line with the concept of environmental protection and sustainable development. DETAILED DESCRIPTION
[0022] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0023] Preparation Example of Silane-Modified Polymer Preparation Example 1 Preparation of silane-modified polymers: Dissolve 10 kg of polyurethane in 30 kg of toluene to form a uniform solution, add 0.6 kg of γ-methacryloxypropyltrimethoxysilane to the polyurethane solution, stir evenly, add 0.05-0.2 kg of diisopropylbenzene peroxide to the mixed solution, control the reaction temperature at 100 ° C, and the reaction time is 3 hours; After the reaction is completed, the solvent is recovered by distillation to obtain a concentrated solution of the silane-modified polymer, and the concentrated solution is vacuum dried to obtain the silane-modified polymer.
[0024] Preparation Example 2 Preparation of silane-modified polymer: The difference from Preparation Example 1 is that 0.4 kg of γ-methacryloxypropyltrimethoxysilane is added to the polyurethane solution.
[0025] Preparation Example 3 Preparation of silane-modified polymer: The difference from Preparation Example 1 is that 0.8 kg of γ-methacryloxypropyltrimethoxysilane is added to the polyurethane solution.
[0026] Preparation example of polymer modified asphalt Preparation Example 4 Preparation of polymer modified asphalt: Heat 200 kg of medium-grained asphalt to 170°C and keep it warm until it is completely melted, add 10-20 kg of styrene-butadiene-styrene block copolymer to the asphalt, and keep stirring for 40 minutes; While maintaining the temperature of the asphalt, add 0.6-2 kg of silane-modified polymer and 0.2-1 kg of diisodecyl phosphite, continue stirring for 15 minutes, then add 2-4 kg of EVA plasticizer, continue stirring for 15 minutes to ensure uniform mixing, and obtain polymer modified asphalt. The silane-modified polymer is prepared by Preparation Example 1.
[0027] Preparation Example 5 Preparation of polymer modified asphalt: The difference from Preparation Example 3 is that the silane modified polymer is prepared by Preparation Example 2.
[0028] Preparation Example 6 Preparation of polymer modified asphalt: The difference from Preparation Example 3 is that the silane-modified polymer is prepared by Preparation Example 3.
[0029] Preparation Example 7 Preparation of polymer modified asphalt: The difference from Preparation Example 3 is that no silane modified polymer is added.
[0030] Preparation Example 8 Preparation of polymer modified asphalt: The difference from Preparation Example 3 is that no diisodecyl phosphite is added. Example
[0031] Example 1 Preparation of a new type of environmentally friendly colored permeable asphalt concrete: In a heating and stirring tank, heat 150kg of polymer modified asphalt to 170°C, add 25kg of red PAC-10 pigment, 250kg of basalt with a particle size of 4-8mm, 450kg of silica sand with a particle size of 1-3mm, and 120kg of basalt fiber with a length of 1-3cm, and stir evenly. During the stirring process, add 80kg of S95 grade mineral powder and 30kg of additives, and stir for 30 minutes to obtain a new type of environmentally friendly colored permeable asphalt concrete.
[0032] Among them, the polymer modified asphalt is prepared by Preparation Example 4, and the auxiliary ingredients are 65% recycled wood pulp and 35% recycled glass powder; the recycled wood pulp is a slurry with a solid content of 60±5% obtained by removing impurities and adding water to crush waste paper and wood; the recycled glass powder is a powder of recycled waste glass ground to 0.05-0.1mm, with a purity of >98%.
[0033] Example 2 Preparation of a new type of environmentally friendly colored permeable asphalt concrete: The difference from Example 1 is that polyphenylene sulfide fiber is used as the reinforcing fiber.
[0034] Example 3 Preparation of a new type of environmentally friendly colored permeable asphalt concrete: The difference from Example 1 is that the reinforcing fiber is a compound of polyphenylene sulfide fiber and basalt fiber in a mass ratio of 1:1.
[0035] Example 4 Preparation of a new type of environmentally friendly colored permeable asphalt concrete: The difference from Example 1 is that quartz sand is used as fine aggregate.
[0036] Example 5 Preparation of a new type of environmentally friendly colored permeable asphalt concrete: The difference from Example 1 is that granite crushed stone is used as coarse aggregate.
[0037] Example 6 Preparation of a new type of environmentally friendly colored permeable asphalt concrete: The difference from Example 1 is that the polymer modified asphalt is prepared by Preparation Example 5.
[0038] Example 7 Preparation of a new type of environmentally friendly colored permeable asphalt concrete: The difference from Example 1 is that the polymer modified asphalt is prepared by Preparation Example 6.
[0039] Comparative Example Comparative Example 1 Preparation of a new type of environmentally friendly colored permeable asphalt concrete: The difference from Example 1 is that the polymer modified asphalt is prepared by Preparation Example 7.
[0040] Comparative Example 2 Preparation of a new type of environmentally friendly colored permeable asphalt concrete: The difference from Example 1 is that the polymer modified asphalt is prepared by Preparation Example 8.
[0041] Comparative Example 3 Preparation of a new type of environmentally friendly colored permeable asphalt concrete: The difference from Example 1 is that no reinforcing fiber is added.
[0042] Comparative Example 4 Preparation of a new type of environmentally friendly colored permeable asphalt concrete: The difference from Example 1 is that no additives are added.
[0043] Performance testing Detection Methods The permeable asphalt concrete prepared in the embodiment and the comparative example was poured into a 100*100*10 cm mold and cured for 28 days. As samples, the radiation heating method was used to heat the samples from 20°C at a rate of 1°C / min, and the temperature when the samples softened was recorded.
[0044] The permeable asphalt concrete prepared in the embodiment and the comparative example was poured into a 100*100*10 cm mold and cured for 28 days. As samples, the samples were placed in a closed environment at 60°C and 70% humidity. The samples were irradiated with ultraviolet lamps to simulate sunlight for 36 hours, and the cracking of the samples was observed and recorded.
[0045] Table 1 Test data statistics Softening temperature / ℃ Cracking Example 1 104.5 Uncracked Example 2 103.4 Uncracked Example 3 105.7 Uncracked Example 4 104.8 Uncracked Example 5 104.0 Uncracked Example 6 102.3 Uncracked Example 7 104.2 Uncracked Comparative Example 1 94.8 Uncracked Comparative Example 2 97.5 Uncracked Comparative Example 3 102.7 Multiple cracks Comparative Example 4 101.5 Slight cracking It can be seen from Example 1 and Comparative Examples 1-2 and Table 1 that the addition of silane-modified polymer and diisodecyl phosphite, as effective antioxidants and stabilizers, can slow down the aging rate of asphalt under conditions of light, oxygen and high temperature, and extend the service life of asphalt.
[0046] Combining Example 1 and Comparative Examples 3-4 with Table 1, it can be seen that the introduction of reinforcing fibers effectively reduces the risk of cracking of permeable asphalt concrete, making the road surface more resistant to the formation and expansion of cracks. The fiber structure of recycled wood pulp helps to enhance the strength and toughness of the material and improve the durability of the road surface. Glass powder can enhance the durability of permeable asphalt concrete.
[0047] It can be seen from Examples 1-3 and Table 1 that no matter basalt fiber and polyphenylene sulfide fiber are added alone or in combination, good anti-cracking effect can be achieved.
[0048] It can be seen from Example 1 and Examples 6-7 and Table 1 that the siloxane group in the silane coupling agent can form a chemical bond with the minerals in the asphalt, while the acrylate group at the other end is compatible with organic polymer materials such as polyurethane. This "bridge" effect significantly enhances the interfacial bonding between polyurethane and inorganic materials such as asphalt, and improves the overall performance of the asphalt mixture. The siloxane segment in the silane-modified polymer has excellent water resistance and weather resistance, and can effectively resist the erosion of moisture, oxygen and ultraviolet rays. This characteristic enables the modified asphalt to maintain good stability and durability under extreme conditions.
[0049] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A new type of environmentally friendly colored permeable asphalt concrete, characterized in that: It includes the following components by weight: 10-20 parts of polymer modified asphalt, 2-3 parts of color pigment, 1-5 parts of additive, 40-50 parts of fine aggregate, 20-30 parts of coarse aggregate, 10-15 parts of reinforcing fiber and 5-10 parts of mineral powder. The polymer modified asphalt is asphalt modified by styrene-butadiene-styrene block copolymer.
2. The new environmentally friendly colored permeable asphalt concrete according to claim 1 is characterized by: The preparation method of the polymer modified asphalt is: Heat the asphalt to 160-180°C and keep it warm to make it completely melted, add 5-10% of the total mass of the asphalt styrene-butadiene-styrene block copolymer to the asphalt, and keep stirring for 30-60 minutes; While maintaining the temperature of the asphalt, add 0.3-1% of the total mass of the asphalt silane-modified polymer and 0.1-0.5% of diisodecyl phosphite, and continue stirring for 10-20 minutes. Then add 1-2% of the total mass of the asphalt EVA plasticizer and continue stirring for 10-15 minutes to ensure uniform mixing to obtain polymer modified asphalt.
3. The new environmentally friendly colored permeable asphalt concrete according to claim 2 is characterized by: The preparation method of the silane-modified polymer is: Dissolve polyurethane in toluene to form a uniform solution, add γ-methacryloxypropyltrimethoxysilane to the polyurethane solution, the addition amount of γ-methacryloxypropyltrimethoxysilane is 4-8% of the mass of the polyurethane, stir evenly, add dicumyl peroxide to the mixed solution, the addition amount of dicumyl peroxide is 0.5-2% of the mass of the polyurethane, control the reaction temperature at 80-120°C, and the reaction time is 2-4h; After the reaction is completed, the solvent is recovered by distillation to obtain a concentrated solution of the silane-modified polymer, and the concentrated solution is dried to obtain the silane-modified polymer.
4. The new environmentally friendly colored permeable asphalt concrete according to claim 1 is characterized by: The reinforcing fibers include one or both of basalt fibers and polyphenylene sulfide fibers.
5. The new environmentally friendly colored permeable asphalt concrete according to claim 1 is characterized by: The fine aggregate is selected from one of silica sand or quartz sand, and the coarse aggregate is selected from one of basalt or granite crushed stone.
6. The new environmentally friendly colored permeable asphalt concrete according to claim 1 is characterized by: The auxiliary agent includes 60-70% recycled wood pulp and 30-40% recycled glass powder. The recycled wood pulp is a pulp obtained by removing impurities from recycled waste paper and wood and adding water to crush them. The recycled glass powder is a powder obtained by grinding recycled waste glass to 0.05-0.1 mm.
7. A method for preparing the new environmentally friendly colored permeable asphalt concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: In the heating equipment, the polymer modified asphalt is heated to 160-170°C, and color pigments, coarse aggregates, fine aggregates, and reinforcing fibers are added and stirred evenly. During the stirring process, mineral powder and additives are added, and after stirring evenly, a new type of environmentally friendly colored permeable asphalt concrete is obtained.
